The nature of hope: grassroots organizing, environmental justice, and political change - Miller, Char, editor; Crane, Jeff, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2018)
Examining the dynamics of environmental activism at the local level and how environmental and political cultures emerge in context of conflict. Considers how ordinary people coalesce to demand environmental justice and highlights the powerful role of intersectionality in shaping the on-the-ground dynamics of protest and social change.--Provided by publisher.
Movement without leaders: how to make change on an overheating planet / Bill McKibben -- An intersectional reappraisal of the environmental justice movement / Brinda Sarathy -- Power to the people: grassroots advocacy, environmental protection, and democratic governance / Cody Ferguson and Paul Hirt -- Returning to the slough: environmental justice in Portland, Oregon / Ellen Stroud -- Streetscape environmentalism: flood control, social justice and political power in modern San Antonio / Char Miller -- When the sky opened: the transformation of Tachikawa Air Base into Showa Kinen Park / Adam Tomkins and Charles Laurier -- Friendship Park: environmental placemaking at the U.S.-Mexico border / Jill M. Holslin -- From bomb to bone: children and the politics of the Nuclear Test Ban Treaty / Jeffrey C. Sanders -- The politics of fear: grassroots knowledge and citizen action in the 1980s / Michael Egan -- Raising change: community farming as long-term ecological protest / Jeffrey Crane -- Building sustainable communities in Los Angeles: intersections of worker power and environmental justice / Anna Kim and Sophia Cheng -- Keeping ore in the ground: protesting Kennecott at Glacier Peak / Adam Sowards -- Oil and water: fracking politics in South Texas / Hugh Fitzsimmons -- New dawn for energy justice in North Carolina / Monica Mariko Embrey -- The Dakota access pipeline, environmental justice, and US settler colonialism / Kyle Powys Whyte.
Keywords: Environmentalism -- United States; Community organization -- United States; Political participation -- United States; Environmental justice -- United States